2019
DOI: 10.1016/j.heliyon.2019.e02086
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigations on Trypanosoma evansi infection in dromedary camels in the South of Algeria

Abstract: An epidemiological study of Trypanosoma evansi ( T. evansi ) infection in dromedaries was conducted in four wilayate (localities) of Southern Algeria: Béchar, El Bayadh, Ouargla, Tamanrasset. Between February 2014 and April 2016, 1056 camels of different ages and both sexes from 84 herds were sampled. The prevalence was determined through parasitological examination (Giemsa stained thin smear, GST), serological tests (CATT/ T. evansi , ELISA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 42 publications
8
24
4
Order By: Relevance
“…No effect of camel age on T. evansi seropositivity was observed in our study. Our finding agrees with some surveys (Boushaki et al 2019 ; Pathak & Khanna 1995 ; Shah et al 2004 ), but differs from those of other research groups who reported increased seroprevalence with increasing age (Atarhouch et al 2003 ; Bogale et al 2012 ; Dia et al 1997 ; Eshetu, Desta & Amare 2013 ; Gutierrez et al 2000 ; Mirshekar, Yakhchali & Shariati-Sharifi 2017 ; Olani et al 2016 ; Tehseen et al 2015 ). In contrast to the above findings, one study in Ethiopia revealed higher infection rates in younger camels than in older adult camels (Lemecha, Lidetu & Hussein 2008 ).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…No effect of camel age on T. evansi seropositivity was observed in our study. Our finding agrees with some surveys (Boushaki et al 2019 ; Pathak & Khanna 1995 ; Shah et al 2004 ), but differs from those of other research groups who reported increased seroprevalence with increasing age (Atarhouch et al 2003 ; Bogale et al 2012 ; Dia et al 1997 ; Eshetu, Desta & Amare 2013 ; Gutierrez et al 2000 ; Mirshekar, Yakhchali & Shariati-Sharifi 2017 ; Olani et al 2016 ; Tehseen et al 2015 ). In contrast to the above findings, one study in Ethiopia revealed higher infection rates in younger camels than in older adult camels (Lemecha, Lidetu & Hussein 2008 ).…”
Section: Discussionsupporting
confidence: 87%
“…In Algeria, T. evansi infection in camels was confirmed for the first time more than a century ago when parasitological examinations discovered that 10% of 282 camels were infected (Sergent & Sergent 1905 ). Outbreaks of trypanosomosis in dromedary herds associated with mortalities and abortions have been documented (Boushaki et al 2019 ). The T. evansi seropositivity rate in our study (49.5%) was higher than previous serological studies conducted in Algeria by Benfodil et al ( 2020 ) and Boushaki et al ( 2019 ), who reported seroprevalence up to 32.4%, and 9.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations